Linearly Polarization-Sensitive Perovskite Photodetectors - Jie Sun; Liming Ding (Nano-Micro Letters, 2023)
Highlights Polarization is an exceptional physical property of light that carries and differentiates a significant amount of optical information. Perovskite materials are utilized in polarization-sensitive photodetectors owing to their crystal structure anisotropy and controllable orientation growth, in addition to their excellent photovoltaic performance. This paper presents an overview of the structural characteristics and photovoltaic performance of different optical structures and low-dimensional perovskite polarization photodetectors. This summary will contribute to the future development of perovskite-based photodetectors that are sensitive to polarization.